Fatores que influenciam a eficiência dos serviços de pós-venda em uma empresa de soluções tecnológicas para o agronegócio - Pistori, Eric Marcel Lemes [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The purpose of this research is to propose and identify opportunities for continuous improvement, aiming to improve the efficiency of services in the after-sales sector of an organization that provides technological solutions for the management of agro-industrial processes in the production of grains and fibers. The work aims, through the analysis of information collected and processed in a Business Intelligence software, to develop computational algorithms capable of identifying bottlenecks in the after-sales sector and exploring opportunities that directly impact the efficiency and quality of service. The exploratory study is divided into two main topics. The first is theoretical in nature and addresses the use of Power BI software (Microsoft®), which assists in the preparation and analysis of data, allowing the creation of reports and visualization dashboards. The second topic presents a case study that integrates data from different sources and sectors of the organization, with the aim of extracting information related to the processes of the after-sales service sector. The identification and control of risks at all levels of the business are essential for knowledge management, promoting actions and practices that are aligned with the organizational strategy. Through detailed analysis of the data collected, it was possible to map the critical activities that directly affect the performance of analysts and the impact generated on the company's operations. The cross-referencing of data from the Topdesk® and GIMB® systems provided a comprehensive view of the performance profile of the analysts and the solutions served, providing valuable subsidies for the reassessment of processes and for the creation of action plans aimed at improving operational efficiency. These actions not only increase the organization's competitive advantage, but also strengthen customer loyalty, ensuring the company's sustainability and growth in the market.

Esta pesquisa tem por propósito propor e identificar oportunidades de melhoria contínua, visando aprimorar a eficiência dos serviços no setor de pós-venda de uma organização que fornece soluções tecnológicas para a gestão de processos agroindustriais na produção de grãos e fibras. O trabalho visa, por meio da análise de informações coletadas e processadas em um software de Business Intelligence, desenvolver algoritmos computacionais capazes de identificar gargalos no setor de pós-venda e explorar oportunidades que impactam diretamente a eficiência e a qualidade do atendimento. O estudo exploratório está dividido em dois tópicos principais. O primeiro é de natureza teórica e aborda a utilização do software Power BI (Microsoft®), que auxilia na preparação e análise de dados, permitindo a criação de relatórios e painéis de visualização. O segundo tópico apresenta um estudo de caso que integra dados de diferentes fontes e setores da organização, com o objetivo de extrair informações relacionadas aos processos do setor de serviços pós-venda. A identificação e o controle de riscos em todos os níveis do negócio são essenciais para a gestão do conhecimento, promovendo ações e práticas que se alinham à estratégia organizacional. Por meio da análise detalhada dos dados coletados, foi possível mapear as atividades críticas que afetam diretamente o desempenho dos analistas e o impacto gerado nas operações da empresa. O cruzamento de dados dos sistemas Topdesk® e GIMB® proporcionou uma visualização abrangente do perfil de desempenho dos analistas e das soluções atendidas, fornecendo subsídios valiosos para a reavaliação de processos e para a criação de planos de ação voltados à melhoria da eficiência operacional. Essas ações não só aumentam a vantagem competitiva da organização, mas também fortalecem a fidelização dos clientes, garantindo a sustentabilidade e o crescimento da empresa no mercado.
Factors Influencing the efficiency of after-sales services in a technology solutions company for agribusiness
Keywords: Clientes fidelização; Gestão de negócios; Mineração de dados (computação); Quantitative business analysis; Agronegócio; Atendimento ao cliente